Digital branding communication model for the Yogyakarta "JIH" Hospital managed by the digital creative agency, Kotakmedia Indonesia - Nur Aswad, Iqbal; Prayudi, Prayudi; Rochayanti, Christina (COMMICAST, 2023)
Marketing communication has progressed quite rapidly; many changes have also occurred in the business industry, including the marketing communication model. In today's all-digital era, digital marketing communications, in this case digital branding, are increasingly being used in promotional activities. One of the most sought-after services in today's digital era is a digital agency. This study analyzes the digital branding communication model on social media at the Yogyakarta "JIH" Hospital, which is managed by the digital creative agency Kotakmedia Indonesia. The purpose of this research is to describe the communication model and management of digital branding on the social media of Yogyakarta "JIH" Hospital, which is managed by the digital creative agency Kotakmedia Indonesia. The research method used is descriptive qualitative with a case study approach. The results of this study indicate that the digital branding communication model for the Yogyakarta "JIH" Hospital, managed by the digital creative agency Kotakmedia Indonesia is effective and has a positive impact on expanding the audience and increasing the company's brand image. As well as successfully obtaining plenary-level hospital accreditation. However, there are several shortcomings that can still be improved, namely, the uneven management of social media. According to social media researchers, attention must be evenly distributed, not only focusing on Instagram but also paying more attention to other social media, namely Facebook, Twitter, and YouTube.